2017
DOI: 10.1111/ene.13258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for cognitive decline in Parkinson's disease: a review of the literature

Abstract: Parkinson's disease is a highly heterogeneous disorder, where genetic factors are likely to contribute to clinical variability, including susceptibility to cognitive impairment and dementia. Monogenic forms of parkinsonism show distinct cognitive profiles, yet less is known about the impact of common genetic variants on cognition in sporadic Parkinson's disease. In a systematic review of the literature, the current results from genetic association studies of cognitive outcomes are summarized and prospects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 88 publications
(72 reference statements)
1
31
0
Order By: Relevance
“…Our model for prediction of CI in PD should, however, be further validated with a larger cohort of drug-naïve PD patients with a longer follow-up period, to permit a correct interpretation in clinical settings. Moreover, additional factors should be considered for future models which could contribute towards clinical outcomes and the prediction of cognitive decline including different genetic profiles which have been shown to play a role in the variability of cognitive outcomes and rates of decline (Fagan and Pilstrom 2017;Liu et al 2017). The inclusion of genetic profiles, into future predictive models of cognitive decline, could be important to facilitate the accurate stratification of PD patients for clinical trials striving towards tailored personalised therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Our model for prediction of CI in PD should, however, be further validated with a larger cohort of drug-naïve PD patients with a longer follow-up period, to permit a correct interpretation in clinical settings. Moreover, additional factors should be considered for future models which could contribute towards clinical outcomes and the prediction of cognitive decline including different genetic profiles which have been shown to play a role in the variability of cognitive outcomes and rates of decline (Fagan and Pilstrom 2017;Liu et al 2017). The inclusion of genetic profiles, into future predictive models of cognitive decline, could be important to facilitate the accurate stratification of PD patients for clinical trials striving towards tailored personalised therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Only 147 participants (across mono-and bilinguals) were APOE ε4 carriers (Ljungberg et al, 2016). Of note, whether APOE ε4 increases the risk of vascular dementia (Rohn, 2014), frontotemporal dementia (Verpillat et al, 2002), dementia with Lewy bodies (Lovati et al, 2010), and Parkinson's disease (Fagan & Pihlstrøm, 2017) is unclear (Lovati et al, 2010). Therefore, adjustment for the APOE ε4 likely did not reach sufficient statistical power (Sham & Purcell, 2014) in this study (Ljungberg et al, 2016) and its clinical relevance to other dementia etiologies may have been limited (Lovati et al, 2010).…”
Section: Group By Diagnosismentioning
confidence: 99%
“…It is highly plausible that the great clinical heterogeneity observed across individual PD patients to some extent reflects differences in underlying genetic architecture, with potential relevance for treatment. [36][37][38] As an example, a recent study reported that the β2-adrenoreceptor is a regulator of SNCA, and that β2 agonist use is negatively associated with PD, suggesting clinical trials of these drugs as a potential neuroprotective therapy. 39 Showing that SNCArelated risk varies by more than 2-fold across quintiles, and that rare homozygotes for the maximum-risk haplotypes may carry 4-fold PD susceptibility compared to the general population, we suggest that patients in the highrisk end of this spectrum would be the most suitable for such clinical trials.…”
Section: Discussionmentioning
confidence: 99%